PROSES PENDIDIKAN DAN PEMBELAJARAN DITINJAU DARI SUDUT PENDIDIK DAN ANAK DIDIK - Daulay, Abdul Sattar (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2013)
Education and learning process that occurs in education, non-formal and informal are  always influenced by certain concepts, because it is begun by how the students perceive the concept.  Emperisme sees that the educational. and developmental outcomes depend on the experiences gained during the students’s protégé. Nativism flow and Naturalism are more on innate factors that it will give freedom to the students to develop and define their development in accordance with the default factor.  Convergence relies flow cooperation congenital factors with environmental factors, so, the educational process is done interactively.  Fitrah concept relies cooperation innate factors with environmental factors, the educational process is conducted interactively although students bring good potential. In this context there are times when the active educators and passive students or in the other hand. However sometimes they must be equally active.